Detection of indoor and outdoor stairs - Shahrabadi, S. (2014)
There are a few applications in which stairs must be detected, for example for aiding blind persons during navigation and for autonomous robots which must rely on vision. . In this paper we present a very simple algorithm for detecting stairs, both in indoor and outdoor environments, when the camera is at a distance of approximately ﬁve meters from the stairs. The problem is hard to solve due to diﬀerent factors like lighting, diﬀerent constructions, materials and view angles. However, ﬁrst results are very promising, although false positive and negative detections cannot yet be avoided.